Efficient nitric oxide sensing on nanostructured La2MMnO6 (M: Co, Cu, Zn) electrodes. Issue 6 (15th March 2023) - Bhardwaj, Aman; Bae, Hohan; Mathur, Lakshya; Mathur, Sanjay; Song, Sun-Ju
Abstract: Selective detection of nitric oxide (NO) is a challenge for automotive exhaust monitoring systems due to the instability of sensing architectures operating under extreme environments. Herein, yttria-stabilized zirconia (YSZ) solid-electrolyte-based electrochemical gas sensor was developed using double perovskite electrodes (DPO) for selective detection of NO. The La2 MMnO6 (M: Co, Cu, Zn) phases were synthesized by sol-gel processing of constituent salts and characterized for physicochemical and sensing properties to investigate the impact of transition metal cations present in octahedral environments on charge transport properties. The La2 ZnMnO6 with a predominant Zn 2+ –Mn 4+ charge ordering excelled in the sensing characteristics with high sensitivity (33 mV/decade for 3–80 ppm NO concentration), fast response/recovery time (52/42 s) and significant NO selectivity at 500 °C. The sensing behavior of double perovskites was comprehensively explored and found to abide by the mixed-potential model. Moreover, stable sensing properties over a period of three weeks indicate the here-described sensors to be potentially competitive for onboard exhaust monitoring in automobiles. Highlights: Double perovskite oxide (DPO) electrodes for nitric oxide (NO) sensor. La2 ZnMnO6 DPO shows sensitivity of 33 mV/decade for 3–80 ppm NO concentration. Response/recovery time of 52/42 s and verified stability over 3 weeks. Sensing mechanism explained by the mixed-potential model.